Building an Entrepreneurial Spirit through Literacy and its Application in Learning in Vocational Schools - Hapsari, Sri; Setiawati, Nur Amega; Munir, Abdul; Ritiauw, Samuel P.; Prasetyono, Hendro (Journal of Vocational Education Studies, 2025)
The learning process in Vocational High Schools (VHS) aims to prepare graduates to be ready for work and entrepreneurship. However, many VHS graduates remain unemployed. To address this issue, students need skills aligned with job market demands and entrepreneurial competencies. This study aims to develop an entrepreneurial spirit in VHS students through literacy and assess their cognitive abilities. The research was conducted at a vocational school in Jakarta using purposive sampling. The method employed was digital ethnography, focusing on student behavior in digital spaces. Data were collected through digital observation and in-depth interviews with two students. The research process included problem identification, literature review, data collection and analysis, and data presentation.Instilling an entrepreneurial spirit is vital to broaden students' perspectives, spark interest in entrepreneurship, and inspire them through stories of entrepreneurial figures. This transformation is supported by comprehensive and continuous entrepreneurial literacy, enhanced by teacher-led taxonomic assessments of learning activities. The study reveals students’ entrepreneurial spirit through literacy initiatives and provides teachers with insight into students' cognitive dimensions in understanding entrepreneurship. These insights enable teachers to design entrepreneurial learning programs that address all levels of the cognitive taxonomy.